2016
DOI: 10.13080/z-a.2016.103.049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water deficit on yield and quality of lemon balm (Melissa officinalis L.)

Abstract: The aim of the present study was to investigate the effect of the level and timing of watering on the productivity and chemical constituents of lemon balm (Melissa officinalis L. cv. 'Soroksár'). As control 70% soil water capacity was set. In treatments stress1 and stress2 the soil water capacity decreased stepwise from 70% to 30% and sharply from 70% to 30%, respectively. In the strongest and permanent water deficit treatment stress3 30% soil water capacity was applied. Among the production parameters the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
3
10
1
Order By: Relevance
“…This might be an explanation to the high FRAP and TPC values of 'Grosso' and higher TPC values of the other Lavandula cultivars from Dörgicse. However, our findings do not correspond to those reported by previous authors (Trócsányi et al, 2015;Németh-Zámbori et al, 2016;Radácsi et al, 2016) concerning drought stress reactions of other xerofil species, such as Thymus vulgaris. According to their results, it was concluded that more polyphenols, such as rosmarinic acid were detected in thyme and lemon balm plants as a consequence of water deficiency, while in our experiment this phenomenon was not observed in the growth year of 2017.…”
Section: 'Grappenhall'contrasting
confidence: 99%
“…This might be an explanation to the high FRAP and TPC values of 'Grosso' and higher TPC values of the other Lavandula cultivars from Dörgicse. However, our findings do not correspond to those reported by previous authors (Trócsányi et al, 2015;Németh-Zámbori et al, 2016;Radácsi et al, 2016) concerning drought stress reactions of other xerofil species, such as Thymus vulgaris. According to their results, it was concluded that more polyphenols, such as rosmarinic acid were detected in thyme and lemon balm plants as a consequence of water deficiency, while in our experiment this phenomenon was not observed in the growth year of 2017.…”
Section: 'Grappenhall'contrasting
confidence: 99%
“…Malejane et al (2018) concluded, based on their trial, that overall, increasing water deficit impacted negatively on the fresh weight of both the green leafy lettuce cultivars tested. Water deficit also reduced the plant height, crown width, fresh and dry mass of Melissa officinalis L. (Radácsi et al 2016). In this study, the number of leaves and stems of S. dolomitica significantly decreased as the water deficits' intensity increased.…”
Section: Discussionsupporting
confidence: 50%
“…The changing shoot/root ratio may reflect an intensive growth of the roots for reaching water in the drier soils, and may also be the result of the reduced shoot growth under unfavourable conditions. Formerly, in a climatic chamber experiment we also found, that water shortage (40% of SWC) resulted in a 2 fold root/shoot ratio of lemon balm compared to the control (Radácsi et al, 2016b).…”
Section: Discussionmentioning
confidence: 61%